Pengaruh Penggunaan Teknologi Kesehatan Terhadap Layanan Kesehatan Di Sekolah - Serri Hutahaean; Nourmayansa Vidya Anggraini; Ruth Mariana Bunga Wadu; Vionita Apriliana; Lutfi Riskyta Istikomah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: Health services are currently very much needed. Especially for school-age children. Objective: This study aims to determine the effect of using health technology, namely mobile applications in improving health services in schools. Methods: This research was conducted at the Holy Faithful Obedient Elementary School Sawangan Depok in October 2022. The respondents in this study were 185 students of SD HFO Sawangan Depok. Data was collected using a questionnaire after being given training related to the use of health technology in the form of a health mobile application. Then the data were analyzed using the Paired t-test to determine the effect of using health technology with school health services. Results: The results showed that the health service before the intervention was 29.98, after the intervention, it increased to 30.76, with a p-value = 0.001 (p < 0.05), meaning that there was a significant effect of the intervention using health technology on improving health services in Indonesia. school. Conclusion: This research can be concluded that there is an improvement in health services in schools after being given training on the use of health technology in the form of school health mobile applications.